THE DYNAMICS OF HUMAN RESOURCE MANAGEMENT IN EDUCATION - Agus Hidayat; Abdul Wahab Syakhrani; Samdani Samdani (Indonesian Journal of Education (INJOE), 2024)
Human resource management (HRM) in education plays an important role in determining the quality and effectiveness of the learning process. This study examines various aspects of the dynamics of human resource management in educational institutions, with a focus on continuous training, recruitment and selection processes, teaching staff welfare and performance evaluation. Continuous training is needed to ensure that teaching staff can adopt the latest technology and develop relevant pedagogical skills. Rigorous recruitment and selection ensures that only competent and dedicated candidates are recruited. The welfare and work-life balance of the teaching force is maintained through various support programmes, while transparent performance evaluations provide feedback for further development. Through this comprehensive approach, the quality of education can be significantly improved.